Single-cell profiling of kinase substrate phosphorylation by single-molecule imaging - Takuya Hidaka; Ryotaro Motoya; Gao Jintian; Sooyeon Kim; Yuichi Taniguchi (PLoS ONE, 2026)
Protein phosphorylation regulates diverse cellular processes, yet its analysis at the single-cell level remains challenging due to the low abundance of phosphoproteins. Here, we present a highly sensitive system for profiling phosphorylation of kinase substrates in individual cells. The method integrates fluorescence labeling of single-cell proteomes, immunoprecipitation using antibodies recognizing phosphorylation within specific amino acid motifs, miniaturized SDS-PAGE, and single-molecule detection using a custom-built light-sheet fluorescence microscope. We applied this approach to analyze substrates of casein kinase 2 (CK2) in HeLa cells treated with the phosphatase inhibitor calyculin A. Bulk and pseudo-single-cell analyses confirmed treatment-induced accumulation of phosphorylated CK2 substrates and demonstrated quantitative performance over biologically relevant input ranges. Importantly, true single-cell measurements revealed heterogeneous phosphorylation patterns across molecular weight regions, highlighting cell-to-cell variability in CK2 signaling that is obscured in bulk analyses. This platform enables profiling of the phosphorylation states of a wide range of kinase substrates in individual cells and provides a foundation for dissecting heterogeneous signaling dynamics.